Medium chain fatty acid ethyl esters – activation of antimicrobial effects by Malassezia enzymes. Issue 4 (10th February 2015) - Mayser, Peter
Summary Free medium and short chain fatty acids are known to have broad antimicrobial activity. However, their practical use in topical therapy is limited by their intensive smell and acidity. Surprisingly, a nearly identical antimicrobial effect was found with the ethyl ester derivatives of these fatty acids, but only against Malassezia (M.) yeast, not against Candida spp. Obviously, these esters are hydrolysed by M. enzymes, thus generating a selective activation of antimicrobial activity especially in areas well populated with these yeast ('targeting'). Octanoic acid ethyl ester (CAS 106‐32‐1) was found to be most suitable. In an agar dilution test, the minimal inhibitory concentrations against M. globosa, M. pachydermatis and M. sympodialis, respectively, ranged between ~5 and 10 mmol l−1 after 10 days of incubation. The effect started immediately and was not delayed by other lipid sources applied simultaneously. Based on these data, fatty acid monoesters may represent a new therapeutic concept in M.‐associated diseases.